A Population of M2 Macrophages Associated With Bone Formation - Olmsted-Davis, Elizabeth; Mejia, Julio; Salisbury, Elizabeth; Gugala, Zbigniew; Davis, Alan R. (Frontiers in Immunology, 2021)
We previously identified transient brown adipocyte-like cells associated with heterotopic ossification (HO). These ancillary cells support new vessel synthesis essential to bone formation. Recent studies have shown that the M2 macrophage contributes to tissue regeneration in a similar way. To further define the phenotype of these brown adipocyte-like cells they were isolated and characterized by single-cell RNAseq (scRNAseq). Analysis of the transcriptome and the presence of surface markers specific for macrophages suggest that these cells are M2 macrophages. To validate these findings, clodronate liposomes were delivered to the tissues during HO, and the results showed both a significant reduction in these macrophages as well as bone formation. These cells were isolated and shown in culture to polarize towards either M1 or M2 similar to other macrophages. To confirm that these are M2 macrophages, mice received LPS which induces proinflammation and M1 macrophages. The results showed a significant decrease in this specific population and bone formation, suggesting an essential role for M2 macrophages in the production of bone. To determine if these macrophages are specific to HO, we isolated these cells using fluorescence-activated cell sorting from a bone defect model, and subjected them to scRNAseq. Surprisingly, the macrophage populations overlapped between the two groups (HO-derived versus callus) suggesting that they may be essential ancillary cells for bone formation in general and not selective to HO. Of further note, their unique metabolism and lipogenic properties suggest the potential for unique cross talk between these cells and the newly forming bone.